Asymmetric formal synthesis of (−)-tetrazomine. Issue 8 (24th February 2021) - Qi, Wei-Yi; Fang, Sheng-Long; Xu, Xue-Tao; Zhang, Kun; Shi, Bing-Feng
Abstract : The asymmetric formal synthesis of (−)-tetrazomine, a structurally unique member of the tetrahydroisoquinoline alkaloids, is presented. Abstract : The asymmetric formal synthesis of (−)-tetrazomine is described. Key features of the synthesis include the efficient synthesis of (2 S, 3 R )-3-hydroxypipecolic acid via a Pd(ii )-catalyzed methylene C(sp 3 )–H acetoxylation, the stereoselective construction of the tetrahydroisoquinoline skeleton via Pd(ii )-catalyzed C(sp 3 )–H monoarylation and Pictet–Spengler reactions, and a Cu(i )-catalyzed exo -selective asymmetric [C + NC + CC] coupling reaction to build the chiral pyrrolidine scaffold.